Pengembangan Multimedia Articulate Storyline 3 Menggunakan Contextual Teaching and Learning - Luthfia Azzahra; Farida Farida; Rizka Pitri (Mandalika Mathematics and Educations Journal, 2023)
COVID-19 has caused a major impact in various fields, one of which is education. The high risk of spreading COVID-19 in the field of education also occurs in Indonesia, which results in learning in schools cannot be carried out face-to-face. This study aims to determine the feasibility and attractiveness of developing multimedia articulate storyline 3 with a contextual teaching and learning approach. Multimedia development articulate storyline 3 using the ADDIE model scheme. The application of articulate storyline 3 multimedia products is applied to 166 grade X students consisting of 102 science students and 64 social studies students, as well as 6 teachers at SMA Negeri 4 Kotabumi. This data analysis technique from the multimedia articulate storyline 3 research uses data analysis validation of media experts and material experts, as well as analysis of teacher and student responses. Based on the results of research on the development of multimedia articulate storyline 3 using contextual teaching and learning, it can be concluded that it is very feasible and very interesting. This is evidenced by the media expert eligibility score of 89.90%, material expert eligibility score of 92.01%, teacher attractiveness score of 91% and students of 93%.